PENGARUH EFISIENSI, KEMUDAHAN, DAN KEAMANAN TERHADAP MINAT NASABAH MENGGUNAKAN LAYANAN TARIK TUNAI TANPA KARTU BANK MANDIRI - Gasperz, Jefry; Lekatompessy, Olive Lidia (JURNAL ILMIAH EDUNOMIKA, 2024)
The Effect of Efficiency, Convenience, and Security on Customer Interest in Using Bank Mandiri Cardless Cash Withdrawal Service. Cardless cash withdrawal is one solution to overcome emergency conditions such as missing a wallet, not carrying cash, or lost or swallowed cards at A.T.M.s. This cardless cash withdrawal service can also be accessed quickly via the Customer’s smartphone. This study aims to empirically examine the effect of efficiency, convenience, and security on customer interest in using cash withdrawal services without bank mandiri cards. This study used quantitative research methods. The sampling technique was accidental sampling. The population and sample were Bank Mandiri K.C.P. Ambon, Pattimura University customers, with 98 respondents. A questionnaire was used to obtain data, and the Likert scale was used as an instrument. Quantitative analysis with S.P.S.S. software version 26.0 was used to analyze data in the preparation of this study. The results of this study are efficiency of providing positive and significant influences, ease of positive and significant influences, security, negative and significant influences, and significant positive influences simultaneously (together) on customer interest in using Bank Mandiri cardless cash withdrawal services.